Geoaccumulation Index and Enrichment Factor of Arsenic in Surface Sediment of Bukit Merah Reservoir, Malaysia - Mohd Ilman Che Abdullah,; Amir Shah Ruddin Md Sah,; Hazzeman Haris, (Tropical Life Sciences Research, 2020)
An investigation study was conducted in Bukit Merah Reservoir (BMR) for the assessment of arsenic concentration in the surface sediment in 23 sampling stations. The sediment samples were digested and analysed for arsenic using Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). Sediment parameters such as pH (4.42 ± 0.71), redox potential (121.77 ± 42.45 mV), conductivity (205.7 ± 64.07 ?S cm–1) and organic matter (25.35 ± 9.34%) were also examined. The main objectives of this study are to determine the arsenic distribution and concentration and at the same time to assess the enrichment of arsenic using the geoaccumulation index (Igeo) and enrichment factor (EF). This study shows the total arsenic concentration in the surface sediment of BMR is 4.302 ± 2.43 mg kg–1 and found to be below the threshold value of Canadian Interim Sediment Quality Guidelines (ISQG). High arsenic concentration is recorded near the southern part of the lake where anthropogenic activities are prevalent. Based on Igeo, 13% of sampling stations are categorised as moderately polluted, 52.2% as unpolluted to moderately polluted and the rest is categorised as unpolluted. EF shows 78.3% stations are classified as extremely high enrichment and the rest as very high enrichment. This finding provides important information on the status of arsenic contamination in BMR and creating awareness concerning the conservation and management of the reservoir in the future. Satu kajian penyelidikan telah dilakukan di Takungan Bukit Merah (BMR) untuk menilai kepekatan arsenik pada permukaan mendapan di 23 stesen pensampelan. Sampel mendapan dicerna dan dianalisa menggunakan Inductively Coupled PlasmaOptical Emission Spectrometry (ICP-OES). Parameter mendapan seperti pH (4.42 ± 0.71), keupayaan redoks (121.77 ± 42.45 mV), kekonduksian (205.7 ± 64.07 µS cm–1) dan jirim organik (25.35 ± 9.34%) juga diuji. Objektif utama kajian ini adalah untuk mengenal pasti taburan dan kepekatan arsenik dan pada masa yang sama menilai pengayaan arsenik menggunakan indeks pengumpulan geo (Igeo) dan faktor pengayaan. Kajian ini menunjukkan jumlah kepekatan arsenik pada permukaan mendapan di BMR ialah 4.302 ± 2.43 mg kg–1 dan didapati di bawah nilai ambang Garis Panduan Kualiti Interim Mendapan Kanada. Kepekatan arsenik yang tinggi direkodkan berhampiran selatan tasik di mana aktiviti antropogen tersebar. Berdasarkan Igeo, 13% daripada stesen pensampelan dikategorikan sebagai sederhana tercemar, 52.2% tidak tercemar kepada sederhana tercemar dan bakinya dikategorikan sebagai tidak tercemar. Faktor pengayaan menunjukkan 78.3% stesen diklasifikasikan sebagai pengayaan yang sangat tinggi dan bakinya agak tinggi. Dapatan ini memberikan maklumat yang penting berkenaan status pencemaran arsenik di BMR dan mewujudkan kesedaran terhadap pemuliharaan dan pengurusan takungan ini di masa hadapan.